Agregação e força de interação cátion-ânion de líquidos iônicos dicatiônicos derivados do imidazol com os ânions ascorbato e ibuprofenato - Paz, Alisson Vasques (2021)
Imidazolium-based ionic liquids (ILs) demonstrate some advantages over the monocationic analogues, as higher fusion temperature, higher thermal stability and less toxicity. Dicationic ILs also form tridimensional aggregates in solution, due to their amphiphilic nature. However, there are still some lacks in the comprehension of the influence of anions with organic structures on the formation of IL aggregates in solution, in the aggregation mechanisms and the intermolecular interactions occurring. This work presents a study of the influence of the chemical structure of ascorbate (Asc) and ibuprofenate (Ibu) anions in the aggregation properties and cation-anion interactions of imidazolium-based ionic liquids containing the cation 1,8-bis(3-methylimidazolium-1-yl)octane ([C8(MIM)2]2+). The aggregation behavior of ILs was evaluated using conductivity, surface tension and Nuclear Magnetic Resonance 1H (NMR 1H). The cation-anion interactions were evaluated using the aggregation by NMR 1H and Surface Plasmon Resonance (SPR). The aggregation results showed that the IL [C8(MIM)2][2Asc] despites being more hydrophilic than [C8(MIM)2][2Ibu], has higher values of critical aggregation concentration (CAC). Both ILs showed lower CAC values than the analogues with bromide anion. The results of aggregation properties by NMR 1H showed that the anions are more concentrated in the interior of the aggregates. The values of ionization degree () determined by conductivity measurements indicate that the LI [C8(MIM)2][2Asc] has a more effective cation-anion interaction. The values of diffusion coefficient by NMR 1H corroborate with conductivity and surface tension data and show that [C8(MIM)2][2Asc] presents an ion pair behavior. The SPR results showed that the IL [C8(MIM)2][2Asc] has a more effective interaction with the titanium dioxide (TiO2) surface, which might be related to the more polar structure of the ascorbate anion. This behavior confirms the ion pair nature of [C8(MIM)2][2Asc]. In conclusion, the anion effect is driven by multiple structural factors besides the apparent hydrophobicity of the IL constituting anions. Besides that, the cation-anion interaction might be a crucial factor on the adherence of ILs on TiO2 surface.